(untitled) (Jurnal Komunikasi Pembangunan, 2023)
This study aimed to determine the effectiveness of the communication strategies used for the business development, to identify the interest of the younger generation, and to analyze the factors that influence the interest in entrepreneurship of the younger generation The research was conducted in Negeri Katon District, Pesawaran Regency, and the study sample consisted of 32 members of the Tapis Jejama Khan MSME group. The study employed a quantitative descriptive method, utilizing the census technique for data analysis. The results indicate that the communication strategies used for the MSME Tapis business development have been effective. The younger generation’s interest in entrepreneurship is high. Furthermore, the study revealed a significant relationship between age, formal education, and motivation with youth interest in entrepreneurship. However, there was no significant relationship between non-formal education, media exposure, agency support, and youth interest in entrepreneurship. In conclusion, the findings of this study suggest the need for continued communication and development efforts to ensure the growth and sustainability of MSMEs. Furthermore, policymakers and MSMEs can focus on developing specific entrepreneurial traits and enhancing formal education to facilitate the regeneration process and keep businesses growing and advancing.